“Nowy Czas” (“New Time”): A Puzzling Journal for the Polish Intelligentsia in the UK (2006–2013) - Chwastyk-Kowalczyk, Jolanta (Respectus Philologicus, 2015)
The article discusses issues published in New Time (Nowy Czas), the free periodical addressed to the Polish intelligentsia in the UK, coming out since 2006 until today in London. It is the only magazine - currently 32-page long monthly - representing the segment of elite cultural and social press for Polish émigré in the United Kingdom, consciously embedded in a wider European political reality. It has an interactive online version: nowyczas.co.uk. The mission of its founders – Grzegorz Małkiewicz and Teresa Bazarnik - is to inform about relevant events in the country and around the world, but above all, to create the Polish community in the UK. The assumed recipient is an educated Pole who is proficient in English and open to biculturalism. The texts written in the islanders' language are intended for the Polish people born in the United Kingdom and their British friends. It is an independent, reliable magazine trusted by the readers. Due to its "over curricular" activities (beyond the scope of regular editorial operations), it has a chance to become the Salon and Advocate of the high culture. The best proof for this argument is the ARTeria appendix. Moreover, New Time engages in pro bono activities in favour of the Polish community living in the British Isles. The most relevant issues, in addition to the widely meant culture, encompass education at all levels and high moral norms giving the readers a sense of the uniqueness of their time, the new time. Finally, there is the first long awaited magazine targeted at educated Poles.
Keywords: Polish Socio-Cultural Magazines in the UK in the 21st Century